Use of a single 2.0-mm locking AO reconstruction titanium plate in linear, non-comminuted, mandible fractures - Parmar, Babu S. (Medknow Publications & Media Pvt Ltd, 2014)
PURPOSE: The aim of the following study is to prospectively evaluate the use of a single Arbeitsgemeinschaft für Osteosynthesefragen (AO) 2.0-mm locking reconstruction plate for linear non-comminuted mandibular fractures without the use of a second plate. MATERIALS AND METHODS: This study consisted of a sample of 10 patients who reported to the department with fractures of the mandible and were treated over a period of 24 months from November 2010 to November 2012. Out of these, there were 8 male patients and 2 female patients. There were four cases of isolated parasymphysis fractures, 1 of the case had a parasymphysis fracture associated with subcondylar fracture, 4 had a body fracture and 2 had a symphysis fracture. RESULTS: All patients had satisfactory fracture reduction and a successful treatment outcome without major complications. Only one patient (10%) developed minor complications. CONCLUSION: The study has demonstrated that treating linear non-comminuted mandibular fractures with a single AO 2.0-mm locking reconstruction plate provides excellent stability at the fracture site which in turn leads to sound bone healing and early functional rehabilitation.